Religion and mergers and acquisitions contracting: The case of earnout agreements - Elnahas, Ahmed M.; Kabir Hassan, M.; Ismail, Ghada M. (Journal of Corporate Finance, 2017)
This paper contributes to the growing literature on the effect of religion on corporate decision making. We posit that contingent payment in mergers and acquisitions not only violates Islamic law but also results in several agency issues by creating an incentive for managers to participate in long-term value-destroying behavior during earnout periods. Our empirical results, using regression as well as difference-in-difference estimation, show that target managers significantly manage earnings upward by cutting discretionary expenses during earnout periods. As compared to a sample of matched non-earnout M&A, acquisitions with earnout clauses are followed by significantly lower long-term abnormal returns. Our arguments and results have significant economic and legal consequences on cross-border M&A and could be used to facilitate worldwide economic integration.